Kosovo’s International Trade: Balance of Trade - Jusufi, Gent; Mahmutaj, Lura Rexhepi; Jusufi, Gentina; Jusufi, Nora (European Journal of Economics and Business Studies, 2015)
Purpose – The purpose of this paper is to present a review of literature on the composition of exports and imports during 2005-2011 in Kosovo and key findings from secondary research on the reasons for the high trade deficit which affects economic development within this country. Design/Methodology/Approach – This paper presents secondary data related to background of the international trade and its increasing importance throughout the years because globalization. Then it is followed by characteristics of Kosovo’s trade environment, its domination of imports from 2005 to 2011 and its comparison with EU and non EU countries. Findings – The results of this paper illustrates that Kosovo is facing a major problem with its negative balance of trade, suffering with excessive volume of imported goods and insufficient exported goods. Kosovo’s trade marked an increase of its exports with annual average growth rate of 36 percent, on the other hand imports marked an increase with annual average growth rate of 13 percent, while the share of exports and imports of GDP was relatively 60 percent by the year of 2011. The reasons of poor export performance are mainly based on social, political, and economical issues that Kosovo is confronting. Nevertheless, government took important macroeconomic steps, as well as developed comprehensive process to review, shift the political and economic policies, to sustain the countries balance of trade in long term.
Keywords: International trade, imports, exports, economic growth